2018
DOI: 10.1525/collabra.132
|View full text |Cite
|
Sign up to set email alerts
|

Improving Human Interaction Research through Ecological Grounding

Abstract: In psychology, we tend to follow the general logic of falsificationism: we separate the 'context of discovery' (how we come up with theories) from the 'context of justification' (how we test them). However, when studying human interaction, separating these contexts can lead to theories with low ecological validity that do not generalize well to life outside the lab. We propose borrowing research procedures from well-established inductive methodologies in interaction research during the process of discovering n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…With the current state of research on Social Agency still very much in the exploratory stage, and there being many methodological considerations to be taken into account, it is advantageous to broaden horizons when considering future research design. A crucial aspect of social psychology research in general is the ecological validity of paradigms (for example, Albert & de Ruiter, 2018;Hermans et al, 2019;Kingstone, Laidlaw, Nasiopoulos, & Risko, 2017;Reader & Holmes, 2016;Risko, Richardson, & Kingstone, 2016;Schlichting et al, 2018); effort must be made to successfully induce a social context. As most social research is screen-mediated to give more experimental control, virtual characters or preprogrammed human stimuli (e.g.…”
Section: Social Agency With Artificial Agentsmentioning
confidence: 99%
“…With the current state of research on Social Agency still very much in the exploratory stage, and there being many methodological considerations to be taken into account, it is advantageous to broaden horizons when considering future research design. A crucial aspect of social psychology research in general is the ecological validity of paradigms (for example, Albert & de Ruiter, 2018;Hermans et al, 2019;Kingstone, Laidlaw, Nasiopoulos, & Risko, 2017;Reader & Holmes, 2016;Risko, Richardson, & Kingstone, 2016;Schlichting et al, 2018); effort must be made to successfully induce a social context. As most social research is screen-mediated to give more experimental control, virtual characters or preprogrammed human stimuli (e.g.…”
Section: Social Agency With Artificial Agentsmentioning
confidence: 99%
“…Yet the heated debates are not without challenges to the desig-nated authority and social bases of the reforms. These challenges include arguments that falsification is not (and should not be) always the objective of empirical research (Albert & de Ruiter, 2018); that replication is not always warranted; that discoveries are sometimes unexpected and beyond what is hypothesized; that expertise entails more than the rule-following execution of research; that hypothesis testing is not the only viable experimental procedure; and that many phenomena are highly sensitive to time and situation and, therefore, can elude repeatable observation via strict rule-following methods. Such disagreements indicate that the understanding of the social will is, at the least, incomplete.…”
Section: Authoritymentioning
confidence: 99%
“…Which of these (or other) models best explains the relation between interactive repair and pragmatic reasoning is an empirical question. Here we have shown that formal models informed by research on human interaction (Albert and Ruiter, 2018) can bring us closer to an understanding of the cognitive and communicative capacities of interacting people. The question of communicative efficiency is inherently one of computational plausibility.…”
Section: Discussionmentioning
confidence: 93%